Bond strength characterization of concrete filled steel tube as structural member - Vinay Kumar Singh; P. K. Gupta; S. M. Ali Jawaid (Electronic Journal of Structural Engineering, 2022)
Studies done by the previous researchers in Concrete Filled Steel Tubes (CFST) have a significant focus on the bond performance of CFST. This paper includes studies on the evaluation of critical parameters such as interface condition, interface length, infilled concrete strength, and end friction and cross-section dimension in these members. It is found that the effect of interface length had very little impact on the bond stress as it shows a promising value when the interface length is in the range of 200-800 mm and after that, it gets shifted and reduced for larger interface length. But this decrease in the bond stress is affiliated with other parameters, like macro-locking, infilled concrete compressive strength distinctly affects the mean interface bond strength for the sample in the regular condition, the interface bond strength for the most part increases with infilled concrete strength. It is spotted that the friction coefficient of 0.15 is used at both column ends to provide the fixity and it becomes clear that the local buckling pattern of the stub column is independent of the end friction. In both categories of columns, the bond strength among the steel tube and infilled concrete reduced extraordinarily with increased cross-sectional dimension.